2014
DOI: 10.1097/bsd.0b013e31826a10b0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Radiographic Analysis of C5 Palsy After Anterior Cervical Decompression and Fusion for Cervical Degenerative Disease

Abstract: This study suggests that improved lordosis of the cervical spinal column can result in traction injury to the spinal cord and C5 nerve roots and that reoperation does not always produce good results. Methods of preventing and treating C5 palsy after anterior decompression and fusion require more evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 24 publications
0
45
1
Order By: Relevance
“…In our series, we had one case (1.5%) with C5 root palsy which is lower than the incidence of Kim et al's [34] series which reported a rate of 4.3%. Incidence of graft extrusion has ranged between 0 and 0.88% [12, 26, 35].…”
Section: Discussioncontrasting
confidence: 59%
“…In our series, we had one case (1.5%) with C5 root palsy which is lower than the incidence of Kim et al's [34] series which reported a rate of 4.3%. Incidence of graft extrusion has ranged between 0 and 0.88% [12, 26, 35].…”
Section: Discussioncontrasting
confidence: 59%
“…Fifty-seven studies [2028,30,3335,3739,4243,45,4748,50,5256,59,6171,7375,7779,82–85,88,89,91–96] containing 355 patients with C5 plasy of 6349 patients after cervical surgery were included. Figure 3 shows that the incidence was 5.3% (95% CI 4.3%–6.2%), with substantial heterogeneity of incidence observed.…”
Section: Resultsmentioning
confidence: 99%
“…22 C5 palsy has been reported mainly after posterior cervical surgery, but can also be seen after surgery using the anterior approach. Kim et al reported that 6 of 134 patients suffered from C5 palsy after anterior cervical discectomy fusion, and 2 patients with C5 palsy had significant weakness of the deltoid muscle (MMT grade 1) 11 ; the authors conducted foraminotomy on these two patients and only one showed full recovery. Hashimoto et al also reported that 17 of 199 patients who underwent anterior decompression surgery and spinal fusion suffered from C5 palsy.…”
Section: Journal Of Orthopaedic Surgery 25(1)mentioning
confidence: 99%
“…Such a complication has been reported mainly after posterior cervical surgery, but has also been documented after surgery via the anterior approach. 11,12 Although many studies on C5 palsy after posterior cervical surgery have been published, the results are often inconclusive and even conflicting. 13,14 Here, we provide a systematic review of the current literature and attempt to analyze the conflicting results among studies to better understand the clinical features, influencing factors, and preventive measures of C5 palsy after posterior cervical surgery.…”
Section: Introductionmentioning
confidence: 99%